The effect of distributive justice climate on virtual team performance: A moderated mediation model - Yu, Xuan; He, Bin; Liu, Meilin; Wang, Ai; Yuan, Yue (Frontiers in Psychology, 2022)
Based on the social interdependence theory, we proposed that the distributive justice climate affects virtual team performance via high-quality relationships, and then we investigated the boundary effect of team proactive personality. The data used in this study were collected in China, including 327 virtual team members that belonged to 75 teams. The following results are obtained: (1) Distributive justice climate and high-quality relationships have significant positive effects on virtual team performance. (2) High-quality relationships mediate the relationship between the distributive justice climate and virtual team performance. (3) Team proactive personality strengthens the direct effect of the distributive justice climate on high-quality relationships. (4) Team proactive personality strengthens the indirect effect of the distributive justice climate on virtual team performance through high-quality relationships. These empirical results have important theoretical significance for team climate construction, personnel selection, and team performance promotion.